Formation of Social and Legal Competencies of Future Social Workers in the Process of Preparation to Work with Young Families - Mykhailyshyn , Halyna; Dovha, Miroslava (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
The problem of professional training of future social workers in the context of formation of necessary knowledge, skills and abilities is actualized in the article. The views of scientists on the content of the notions of competency, competences and professional competency of social workers are considered. The author's definitions of “competency”, “competences”, “professional competency” and “social and legal competency” are also suggested. Professional competency is the formation of various components, a system of certain components and personality and psychological properties of the individual, which includes knowledge, skills, abilities, personal characteristics and organizational and pedagogical conditions for training future specialists. The main components of socio-legal competencies are identified: cognitive, activity-operative, motivational, personal and instrumental. It also identifies the types of social and legal knowledge that future social workers will receive in the course of their professional training and the skills and abilities of their professional activity. Knowledge of social and legal activity for work with young families was divided into types by the following criteria: socio-legal knowledge in the fields of law, socio-legal knowledge obtained by the degree of their hierarchy in legislation, socio-legal knowledge of the degree of formation, social and legal knowledge on the degree of use of the acquired information. In addition, the acquired knowledge and skills of social and legal activity, which is an activity-operational component of social and legal competency, are accordingly formed in relation to the acquired social and legal knowledge: individual organizational skills, skills and abilities in forecasting and design work, skills and counseling skills. An instrumental component of the formation of complex knowledge of social and legal activity is suggested where social design as a modern progressive tool for overcoming social problems in dealing with young families was highlighted. A social project called “Education for a Young Family” was developed. It is proved that without all the components, social and legal activity will not be fully implemented and social and legal competency will be impossible to develop.